Assessing the effect of discipline on academic performance at Ejisu Senor High Technical School and Atwima Kwanwoma Senior High School. - Boateng, Rita (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Award Of Master Of Arts In Sociology.